Role of NASA 10-minute Lean Test in diagnosing postural orthostatic tachycardia syndrome: a preliminary study in young population - Musharaf Bashir; Himani Ahluwalia; Tazeen Khan; Sheikh Imran Sayeed (Italian Journal of Medicine, 2021)
Postural orthostatic tachycardia syndrome (POTS) is a form of autonomic imbalance characterized by abnormally increased heart rate (HR) and various symptoms of orthostatic intolerance (OI). This study aimed to determine POTS in adolescents using NASA 10-minute Lean Test. This crosssectional study was conducted at Government Medical College, Srinagar, J&K, India, between October 2017 and November 2019. Adolescents with symptoms of OI were enrolled for this study and NASA 10-minute Lean Test was performed. Characteristics of POTS group were the compared with non-POTS group. There was a significant difference in BMI (P< 0.0001) between POTS and non-POTS group. However, the number of females with features of POTS was greater than males. There was a significant difference in resting HR between the two groups (P<0.0001). During upright posture there was a significant difference in maximum upright HR between the two groups (P<0.0001), highest increment in upright HR also differed significantly (P<0.0001).POTS group had significantly higher HR than non-POTS group. It may be inferred from this preliminary study that NASA 10-minute Lean Test can be used to diagnose POTS.